137k views
3 votes
Part A: if k is a constant, show that a general (one-parameter) solution of the differential equation dx/dt = kx^2 is given by x(t) = 1/(C-kt), where C is an arbitrary constant. Part B: Determine by inspection a solution of the initial value problem dx/dt = kx^2, x(0) = 0.

User Daniel Dao
by
4.9k points

2 Answers

4 votes

Final answer:

We demonstrated that x(t) = 1/(C-kt) is a solution to the differential equation dx/dt = kx^2 by taking the derivative and showing it matches the original equation. For the initial value problem where x(0) = 0, x(t) = 0 for all t is a solution.

Step-by-step explanation:

To show that x(t) = 1/(C-kt) is a solution to the differential equation dx/dt = kx2, we can take the derivative of x(t) with respect to t and substitute it back into the original differential equation.

  1. Take the derivative of x(t) with respect to t, which gives us dx/dt = k/(C-kt)2.
  2. Substitute x(t) into the right-hand side of the original differential equation to get kx2 which simplifies to k/(C-kt)2.
  3. Since the derivative of x(t) and kx2 are equal, x(t) = 1/(C-kt) is indeed a solution to the differential equation.

For Part B, by inspection, if x(0) = 0, then C must be zero to satisfy the initial condition. Therefore, the solution to the initial value problem is x(t) = 0 for all t.

User Paolo RLang
by
5.1k points
2 votes

Answer:

A.x(t) =
(1)/(C-kt)[\tex] satisfies the differential equation</p><p></p><p></p><p><strong>Step-by-step explanation:</strong></p><p>To show that [tex](1)/(C-kt)[\tex] is a solution on one hand we derive the function and on the other we square it and multiply the constant k.</p><p>[tex](dx)/(dt) = (d)/(dt)(1)/(C-kt) =((-1).(-k))/((C-kt)^(2) )=(k)/((C-kt)^(2) )

k.x²=
k.({(1)/(C-kt)})^(2) ={(k)/((C-kt)^(2))

User Mark Horgan
by
4.8k points